Efek Suplementasi ENERVON-C dan SANTA-e dalam Pakan terhadap Motilitas Spermatozoa Ayam Kampung - Triva Murtina Lubis; Dasrul Dasrul; Hamdan Hamdan; Fauziah Fauziah (Agricultural Faculty, 2012)
Effect of Supplementation of ENERVON-C and SANTA-e in Feed on Sperm Motility of Local CocksABSTRACT. This study aimed to observe the effect of supplementation of ENERVON-C and SANTA-e in feed on sperm motility of local cocks. The research was conducted at Reproduction Laboratory, Faculty of Veterinary Medicine, Syiah Kuala University, Banda Aceh. The research used 12 local cocks divided into 4 treatment groups : P0 (feed of 521), P1 (feed of 521 + 200 mg ENERVON-C/kg of feed), P2 (feed of 521 + 200 mg SANTA-e/kg feed) and P3 (feed of 521 + 100 mg ENERVON-C/kg of feed and 100 mg SANTA-e/kg of feed). During the research, all cocks were given 100 g of 521 feed/day. Feed with ENERVON-C and SANTA-e was given for 2 weeks before semen collections. Drink was given ad libitum. Data were analysed with analysis of variance and if there are effects among the treatments, analysis will be continued with Duncan Test. Results shows that supplementation of ENERVON-C or SANTA-e and their combination in feed can increase the percentage of sperm motility. There are significant differences (p0,05) between control and treatment groups. To sum up, supplementation of ENERVON-C or SANTA-e in feed can improve the quality of sperm (motility) of local cocks. The sperm quality is better after giving of ENERVON-C and SANTA-e together than single supplementation.